Local Food Systems in Cambodia, Myanmar, and the Philippines: Perspective from the Local Communities - Espino, Apple; Monville-Oro, Emilita; Barbon, Wilson John; Ruba, Christine Dianne; Gummadi, Sridhar; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Food systems must provide adequate, healthy, and sustainable diets to the growing and changing population whilst responding to shocks and stressors related to climate variability, urbanization, globalization, conflicts, and economic change. This study examined the national food systems of Cambodia, Myanmar, and the Philippines and the local food systems of complementary Climate-Smart Villages: Chhouk, Htee Pu, and Himbubulo Weste.